2021
DOI: 10.5194/tc-2021-303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A regionally resolved inventory of High Mountain Asia surge-type glaciers, derived from a multi-factor remote sensing approach

Abstract: Abstract. Knowledge about the occurrence and characteristics of surge-type glaciers is crucial due to the impact of surging on glacier melt and glacier related hazards. One of the "super-clusters" of surge-type glaciers is the mountains of Asia. However, no consistent region-wide inventory of surge-type glaciers in High Mountain Asia exists. We present a regionally resolved inventory of surge-type glaciers based on their behaviour across High Mountain Asia between 2000 and 2018. We identify surge-type behaviou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Surge type glaciers inventory from Guillet et al (2022) The code to reproduce the results can be found on github (https://github.com/pohleric/barandun_pohl_tsl-correl). The required main input files, containing the morphological and meteorological data are deposited on a zenodo repository (https://doi.org/10.5281/zenodo.6631963).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surge type glaciers inventory from Guillet et al (2022) The code to reproduce the results can be found on github (https://github.com/pohleric/barandun_pohl_tsl-correl). The required main input files, containing the morphological and meteorological data are deposited on a zenodo repository (https://doi.org/10.5281/zenodo.6631963).…”
Section: Discussionmentioning
confidence: 99%
“…We use glacier outlines and areas from the RGIv6 (RGI, 2017), which were kept unchanged over time, and the freely available, void-filled Shuttle Radar Topography Mission (SRTM, Jarvis et al, 2008) digital elevation model to derive glacier topography, aspect and slope as morphological parameters. We use further the information provided in Scherler et al (2018) on percentage of debris-cover on individual glaciers for the Tien Shan and Pamir and the data on surge activity from (Guillet et al, 2022).…”
Section: Glacier Morphological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the velocity data used in Guillet et al. (2022) is annual scale data extracted from optical images. The elevation data also has the problem of a too long time interval.…”
Section: Introductionmentioning
confidence: 99%
“…Guillet et al. (2022) identify surge‐type glaciers by using multiple factors, including surface velocity, elevation and feature changes in High Mountain Asia. However, the velocity data used in Guillet et al.…”
Section: Introductionmentioning
confidence: 99%